Back Cover: Ultrashort Broadband Cooperative Pulses for Multidimensional Biomolecular NMR Experiments (Angew. Chem. Int. Ed. 44/2018). Issue 44 (15th October 2018) - Asami, Sam; Kallies, Wolfgang; Günther, Johannes C.; Stavropoulou, Maria; Glaser, Steffen J.; Sattler, Michael
Abstract : Cooperative (COOP) pulses, designed to compensate each other's imperfections, can significantly boost the performance of NMR experiments. S. Asami, S. J. Glaser, M. Sattler et al. demonstrate in their Communication onpage 14498 that pairs of COOP π/2 pulses greatly improve commonly used biomolecular NMR experiments by lighting up the entire spectral range of interest at ultra‐high magnetic fields. Here, an optimized pair of COOP pulses is visualized by representing the time‐dependent phase by the orientation of radial bars (in blue).